Short-term Survival in Renal Transplantation from Brain-Death Donors: Focusing on Recipients with Diabetes Background - Nakhjavani, Manoochehr; Ghaemi, Fatemeh; Ravaghi, Hamid; Aghighi, Mohammad; Ghaemi, Farahnaz (Urology Journal, 2014)
Abstract Purpose: Our aim was to evaluate short term survival rates in renal transplant recipients from deceased donors, while focusing on recipients with diabetes mellitus background. Materials and Methods: This is a longitudinal follow-up study based on national registry of recipients in Ministry of Health and Medical Education in Iran from 2010-11. Five hundred fifty-five recipients, 226 (40.8%) females and 328 (59.2%) males, were included in the study. Mean (± SD) age of the recipients was 39 ± 14 years. Of donors 18.4% were females and 81.6% were males. Age of the donors was 33 ± 14 years. All allograft recipients from deceased donors enrolled in the study. Short-term graft survival (1 year) was determined. Data regarding age, gender, background disease and cold ischemic time of recipients and donors were collected from the organ procurement units. Results: Allografts were functioning in 499 (90.1%) of recipients after one year. Of recipients 38 (6.9%) died and rejection of transplanted kidney occurred in 17 (3.1%) cases. So, in 55 (9.9%) cases, allografts were not functioning. There were significant relationships between short term graft survival of donors' gender, age of recipients, cold ischemic time and level of clearance of creatinine of recipients. Conclusion: In addition to cold ischemic time, graft survival can be affected by recipients' age. There are some other considerations and implications regarding the short term graft survival in renal transplantation from cadaver donors which are discussed in this paper.